Sicurezza a scala territoriale: il ruolo degli strumenti di supporto alle decisioni - Stefano Marsella; Marcello Marzoli (GEOmedia, 2019)
The problems to be overcome to deal with emergency situations in case of natural disasters can be many and, especially in recent years, require specific skills in various areas. In particular, in-depth knowledge of all those platforms that can support decisions to be taken in risk situations is increasingly necessary: the so-called DSS (Decision Support Tools). Let's see which are the limits of current emergency plans on a territorial scale, how they can be improved and the role of decision support tools.